Die südägäische Inselbrücke - Creutzburg, Nikolaus (ERDKUNDE, 1966)
Recent investigations in the Cretan islands arc have made it necessary to distinguish stratigraphically in principle between sedimentary basic series and overlying series, the former mainly Paleozoic, partly early Mesozoic, the latter Mesozoic to early Tertiary, generally not metamorphous. The evidence allows conclusions to be drawn concerning both the paleogeographic situation as well as the tectonic structure. The rocks of the basic series come to the surface to a large extent only in the central section of the island arc, viz. Crete-Kasos, whereas they are of little importance in the north western section (Kythera) and missing altogether in the north eastern one (Karpathos-Rhodos). This means that the vertical components of the more recent tectonic movements must have been considerably greater in the central section of the arc than on its wings. In the central section this led not only to a pronounced tectonic uplift but also to the erosion of most of the younger overlying strata. For the possible cause of the formation of the island arc and the uneven tectonic uplift, Harrison's hypothesis of 1956 (gravity anomalies in the eastern Mediterranean) is referred to. The paper attempts further to sketch the paleogeographic development of the entire island arc as far as the present state of knowledge will allow.